The theology of Paul the Apostle - Dunn, James Douglas Grant, 1939- (Grand Rapids, MI Eerdmans, 1998)
Includes bibliographical references and index.
Keywords: Bible. N.T. Epistles of Paul -- theology; Paul, the Apostle, Saint